Bilateral choroidal metastasis from carcinoma of the submandibular gland - John Sheeja; Horo Saban; Braganza Andrew; Kuriakose Thomas (Indian Journal of Ophthalmology, 2008)
Metastatic tumor is the most common uveal malignancy. However, choroidal metastasis from a salivary gland neoplasm is extremely rare. We report a case of bilateral, multifocal choroidal metastasis from carcinoma of the submandibular gland.